Спортивная периодика Украины и Иракского Курдистана как средство становления национального единства в переходный период (Journal of the College of Languages (JCL), 2013)
In this subject article analyzed features of a sports indifferent countries during , article analyzed features of a sports media in different countries between social change politcheskih , transformation thematic area dedicated sports periodicals and the influence of these media on the formation of national identity .Subject of comparative analysis research are sports print media in Ukraine and Iraqi Kurdistan .And highlight the sports as one of modem Kurdish journalism in lraqi Kurdistan that emerged after the spring in 1991 which took her privacy in the field of journalism , and analysis with sports journalism in the era of the independent state of Ukнаraine in the early nineties of the past century .